The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1089/neu.2019.6912
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Mortality for the Elderly with Acute Traumatic Spinal Cord Injury

Abstract: As the incidence of traumatic spinal cord injury (tSCI) in the elderly rises, clinicians are increasingly faced with difficult discussions regarding aggressiveness of management, likelihood of recovery, and survival. Our objective was to outline risk factors associated with in-hospital mortality in elderly surgical and non-surgical patients following tSCI and to determine those unlikely to have a favorable outcome. Data from elderly patients (≥ 65 years of age) in the Canadian Rick Hansen SCI Registry from 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 41 publications
3
45
1
Order By: Relevance
“…Based on our results, in patients treated surgically, a poor general condition with a greater number of comorbidities was considered to result in an increase in postoperative complications or poor postoperative recovery, and hence an increased mortality risk. Previously, a neurological de cit has been linked to mortality after a cervical fracture in the elderly [1-3, 6, 13] and mortality has been correlated with the severity of a neurological de cit [13,14]. The results of our study supported the same nding.…”
Section: Discussionsupporting
confidence: 90%
“…Based on our results, in patients treated surgically, a poor general condition with a greater number of comorbidities was considered to result in an increase in postoperative complications or poor postoperative recovery, and hence an increased mortality risk. Previously, a neurological de cit has been linked to mortality after a cervical fracture in the elderly [1-3, 6, 13] and mortality has been correlated with the severity of a neurological de cit [13,14]. The results of our study supported the same nding.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported several predictors of mortality in TSCI, such as age, neurological level, severity of neurological deficits, comorbidities, presence of other injuries, and ventilation status (7,(14)(15)(16)(17). However, the sample sizes of most studies did not yield convincing findings, and their long time span involving changes in treatment may have affected the analysis.…”
Section: Introductionmentioning
confidence: 97%
“…comorbidities) and care practices (e.g. surgery, ventilation) influence mortality risk in the elderly [45]. Future work should consider developing additional algorithms and tools to provide a more precise prediction during the patient's admission for these factors and consider other outcomes (e.g.…”
Section: Discussionmentioning
confidence: 99%